Plastic scintillator and preparation method thereof

Traditional light guide enhancement is solved by using a combination of polymethylphenylsiloxane with polymethylphenylmethylhydrosiloxane copolymer, fluorescent dye and dimethylsiloxane light guide enhancer in plastic scintillators The light loss and physical damage caused by the agent achieve more efficient light collection and more stable optical signal transmission, improving detection performance and service life.

CN119192847AInactive Publication Date: 2024-12-27CHAOYANG BIOTECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411298086.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional plastic scintillators have problems with light loss and physical damage in light guide enhancement, and the dispersion uniformity and stability of the light guide enhancer are insufficient, which affects the light transmission effect.

Method used

The copolymer of polymethylphenylsiloxane and polymethylphenylmethylhydrosiloxane is used as the matrix, and the 3-(benzoxazole)-6-(phenyl)benzoxazole fluorescent dye is combined with 1,4-bis(5-phenyloxazole) benzene wave transfer agent and dimethylsiloxane light guide enhancer prepare plastic scintillators through a thermal curing process in a vacuum environment to improve the light transmission efficiency.

Benefits of technology

It significantly improves the transmission efficiency of photons, reduces light scattering and absorption, enhances light collection ability, improves the detection performance of scintillators, and extends service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005046722930000071
    Figure BDA0005046722930000071
  • Figure BDA0005046722930000081
    Figure BDA0005046722930000081
Patent Text Reader

Abstract

The invention relates to the technical field of plastic scintillators, and discloses a plastic scintillator and a preparation method thereof, the plastic scintillator comprises a matrix, a fluorescent dye, a wave shifter and a photoconductive enhancer; the matrix is a copolymer of polymethylphenylsiloxane and polymethylphenylmethylhydrosiloxane; the fluorescent dye is 3-(benzoxazole)-6-(phenyl) benzoxazole; a wave moving agent: 1, 4-bis (5-phenyl oxazole) benzene; and a photoconductive enhancer: dimethyl siloxane; and the mass of the photoconductive reinforcing agent is 0.1-0.3% of the mass of the plastic scintillator. According to the invention, dimethyl siloxane is introduced into a matrix as a photoconductive enhancer, so that the light collection efficiency is effectively improved, the optical transparency and stability of the scintillator are improved, and the scintillator shows more excellent performance in applications such as high-energy particle detection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of plastic scintillators, and in particular to a plastic scintillator and a preparation method thereof. Background Art

[0002] Plastic scintillator is a solid material with a polymer as the matrix and scintillating materials added. When various charged particles enter the scintillator, the scintillating materials will be stimulated to emit fluorescence. These fluorescences are detected by photosensitive devices, thereby realizing the detection of charged particles. There are generally two ways to collect fluorescence. One is to use a light guide to collect photons into a photosensitive device; the other is to collect light into the optical fiber through a wavelength-shifting optical fiber, and use the characteristics of the total reflection angle of the wavelength-shifting optical fiber to propagate the light in the radial direction of the optical fiber and collect it in the photosensitive device.

[0003] Traditional photoconductivity enhancers are usually used in optical fibers or optical coatings to improve light collection capabilities, but these methods often require additional processing steps and may cause light loss or physical damage to the optical fibers. In addition, the dispersion uniformity and stability of photoconductivity enhancers in plastic scintillators also have a significant impact on the light transmission effect. Summary of the invention

[0004] In view of this, the present invention provides a plastic scintillator and a preparation method thereof.

[0005] In one aspect, a plastic scintillator provided by the present invention comprises: a matrix, a fluorescent dye, a wave shifter, and a photoconductivity enhancer;

[0006] Matrix: copolymer of polymethylphenylsiloxane and polymethylphenylmethylhydrogensiloxane;

[0007] Fluorescent dye: 3-(Benzoxazole)-6-(phenyl)benzoxazole;

[0008] Wave shifter: 1,4-bis(5-phenyloxazole)benzene;

[0009] and photoconductivity enhancers: dimethylsiloxane;

[0010] The light guide enhancer accounts for 0.1-0.3% of the mass of the plastic scintillator.

[0011] Furthermore, the mass ratio of polymethylphenylsiloxane to polymethylphenylmethylhydrogensiloxane in the matrix is ​​8:2.

[0012] Furthermore, the molecular weight of the polymethylphenylsiloxane is 10000-30000, and the molecular weight of the polymethylphenylmethylhydrogensiloxane is 5000-20000.

[0013] Furthermore, the fluorescent dye accounts for 5-7% of the mass of the plastic scintillator, and the wave shifter accounts for 0.05-0.15% of the mass of the plastic scintillator.

[0014] On the other hand, the present invention provides a method for preparing the above-mentioned plastic scintillator, comprising the following steps:

[0015] Mixing polymethylphenylsiloxane and polymethylphenylmethylhydrogensiloxane at a mass ratio of 8:2 and stirring for 30-60 minutes to obtain component A;

[0016] Dissolving a fluorescent dye, a wave shifter and a photoconductivity enhancer in an organic solvent to obtain component B; stirring the component A and component B under a vacuum environment for 1-2 hours to obtain a mixed solution; placing the mixed solution in a vacuum degassing tank, and using a vacuum pump to extract bubbles in the liquid;

[0017] Benzoyl peroxide is added as a catalyst and placed in a mold for thermal curing to obtain the plastic scintillator.

[0018] Furthermore, the organic solvent is toluene or xylene.

[0019] Furthermore, the vacuum degree in the vacuum degassing tank is adjusted to 50-100 Pa, and the degassing time is 30-60 min.

[0020] Furthermore, the amount of benzoyl peroxide used is 0.5-1% of the total mass of the mixed solution.

[0021] Furthermore, in the thermal curing, the initial temperature is 35-40°C, the heating is performed at a heating rate of 10-15°C / h, and the heating time is 4-6h.

[0022] Furthermore, the thermal curing is performed in a sealed environment.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] By adding the photoconductivity enhancer dimethylsiloxane to the matrix, the transmission efficiency of photons in the plastic scintillator is significantly improved. This design reduces light scattering and absorption, thereby enhancing the light collection capability and improving the detection performance of the scintillator. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Example 1

[0027] Matrix: polymethylphenylsiloxane and polymethylphenylmethylhydrogensiloxane, mass ratio 8:2.

[0028] Fluorescent dye: 3-(benzoxazole)-6-(phenyl)benzoxazole, the content of which is 6% of the mass of the plastic scintillator.

[0029] Wave shifter: 1,4-bis(5-phenyloxazole)benzene, the content is 0.1% of the mass of the plastic scintillator.

[0030] Photoconductivity enhancer: dimethylsiloxane, the content is 0.2% of the mass of the plastic scintillator.

[0031] Preparation method:

[0032] The base ingredients were mixed and stirred for 30 minutes.

[0033] The fluorescent dye, the wavelength shifter and the photoconductivity enhancer are dissolved in toluene to obtain component B.

[0034] Component A and component B were stirred under vacuum for 1.5 hours and placed in a vacuum degassing tank for degassing for 40 minutes.

[0035] 0.8% of benzoyl peroxide catalyst was added and thermal curing was carried out (initial temperature 35° C., heating rate 10° C. / hour, heating time 5 hours).

[0036] Example 2

[0037] Matrix: polymethylphenylsiloxane and polymethylphenylmethylhydrogensiloxane, mass ratio 8:2.

[0038] Fluorescent dye: 3-(benzoxazole)-6-(phenyl)benzoxazole, the content of which is 7% of the mass of the plastic scintillator.

[0039] Wave shifter: 1,4-bis(5-phenyloxazole)benzene, the content is 0.1% of the mass of the plastic scintillator.

[0040] Photoconductivity enhancer: dimethylsiloxane, the content is 0.3% of the mass of the plastic scintillator.

[0041] Preparation method:

[0042] The base ingredients were mixed and stirred for 45 minutes.

[0043] The fluorescent dye, the wavelength shifter and the photoconductivity enhancer are dissolved in xylene to obtain component B.

[0044] Component A and component B were stirred under vacuum for 1 hour and degassed for 45 minutes.

[0045] 0.7% benzoyl peroxide catalyst was added and thermal curing was carried out (initial temperature 36° C., heating rate 12° C. / hour, heating time 5 hours).

[0046] Example 3: Optimizing Configuration

[0047] Matrix: polymethylphenylsiloxane and polymethylphenylmethylhydrogensiloxane, mass ratio 9:1.

[0048] Fluorescent dye: 3-(benzoxazole)-6-(phenyl)benzoxazole, the content of which is 5% of the mass of the plastic scintillator.

[0049] Wave shifter: 1,4-bis(5-phenyloxazole)benzene, the content is 0.1% of the mass of the plastic scintillator.

[0050] Photoconductivity enhancer: dimethylsiloxane, the content is 0.15% of the mass of the plastic scintillator.

[0051] Preparation method:

[0052] The base ingredients were mixed and stirred for 60 minutes.

[0053] The fluorescent dye, the wavelength shifter and the photoconductivity enhancer are dissolved in toluene to obtain component B.

[0054] Component A and component B were stirred under vacuum for 1 hour and degassed for 35 minutes.

[0055] 0.6% of benzoyl peroxide catalyst was added and thermal curing was carried out (initial temperature 37° C., heating rate 11° C. / hour, heating time 5 hours).

[0056] Comparative Example 1

[0057] Matrix: polymethylphenylsiloxane and polymethylphenylmethylhydrogensiloxane, mass ratio 8:2.

[0058] Fluorescent dye: 3-(benzoxazole)-6-(phenyl)benzoxazole, the content of which is 6% of the mass of the plastic scintillator.

[0059] Wave shifter: 1,4-bis(5-phenyloxazole)benzene, the content is 0.1% of the mass of the plastic scintillator.

[0060] Traditional optical enhancer: optical fiber, the content is 0.2% of the mass of plastic scintillator.

[0061] Preparation method:

[0062] The base ingredients were mixed and stirred for 30 minutes.

[0063] The fluorescent dye, the wavelength shifter and the optical fiber are dissolved in toluene to obtain component B.

[0064] Component A and component B were stirred under normal conditions for 2 hours.

[0065] Direct heat curing without vacuum degassing step.

[0066] Comparative Example 2: Traditional silica photoconductive agent

[0067] Matrix: polymethylphenylsiloxane and polymethylphenylmethylhydrogensiloxane, mass ratio 8:2.

[0068] Fluorescent dye: 3-(benzoxazole)-6-(phenyl)benzoxazole, the content of which is 5% of the mass of the plastic scintillator.

[0069] Wave shifter: 1,4-bis(5-phenyloxazole)benzene, the content is 0.1% of the mass of the plastic scintillator.

[0070] Traditional photoconductivity enhancer: silicon dioxide, the content is 0.2% of the mass of plastic scintillator.

[0071] Preparation method:

[0072] The base ingredients were mixed and stirred for 30 minutes.

[0073] The fluorescent dye, the wavelength shifter and the silicon dioxide are dissolved in xylene to obtain component B.

[0074] Component A and component B were stirred under normal conditions for 2 hours.

[0075] Direct heat curing without vacuum degassing step.

[0076] Comparative Example 3

[0077] Matrix: polymethylphenylsiloxane and polymethylphenylmethylhydrogensiloxane, mass ratio 8:2.

[0078] Fluorescent dye: 3-(benzoxazole)-6-(phenyl)benzoxazole, the content of which is 6% of the mass of the plastic scintillator.

[0079] Wave shifter: 1,4-bis(5-phenyloxazole)benzene, the content is 0.1% of the mass of the plastic scintillator.

[0080] Photoconductive coating: Photoconductive coating, content is 0.2% of the mass of plastic scintillator.

[0081] Preparation method:

[0082] The base ingredients were mixed and stirred for 30 minutes.

[0083] The fluorescent dye, the wavelength shifter and the photoconductive coating are dissolved in toluene to obtain component B.

[0084] Component A and component B were stirred under normal conditions for 2 hours.

[0085] Direct heat curing without vacuum degassing step.

[0086] It should be noted that in the above embodiments, polymethylphenylsiloxane (PMPS) and polymethylphenylmethylhydrogensiloxane (PMHS) are two siloxane polymers with good thermal stability and mechanical strength. By copolymerizing these two polymers, a matrix with excellent mechanical properties and thermal stability can be obtained. PMPS has high heat resistance and good transparency, while PMHS can provide higher flexibility and better fluidity. Their copolymerization can achieve a combination of these properties, thereby improving the overall performance of the plastic scintillator.

[0087] The copolymer of these two polymers exhibits excellent optical transparency and can effectively conduct the light signal generated by the scintillator without introducing excessive light scattering or absorption. This is crucial for the application of plastic scintillators, because good optical transparency ensures that the light signal can be transmitted to the photosensitive detector as much as possible, thereby improving the sensitivity and accuracy of detection. Both polymethylphenylsiloxane and polymethylphenylmethylhydrogensiloxane have strong chemical stability and corrosion resistance, which enables the copolymer to maintain stable performance under various environmental conditions. They are insensitive to chemical reagents, humidity and temperature changes, which helps to extend the service life of plastic scintillators. This copolymer combination has good processing properties, including low viscosity and good fluidity, which enables uniform material mixing and stable molding during the preparation process. This is particularly important for large-scale production and the manufacture of complex shapes.

[0088] Fluorescent dye: 3-(Benzoxazole)-6-(phenyl)benzoxazole (POPOP) is a dye with excellent fluorescence emission characteristics. When excited by high-energy charged particles, POPOP can emit strong and stable fluorescence. This strong fluorescence emission can ensure that the plastic scintillator generates sufficient light signals during the detection process, thereby improving the sensitivity of detection. POPOP has good wavelength selectivity and can emit light signals in a specific wavelength range, which is crucial for matching the wavelength response characteristics of photosensitive detectors. The appropriate wavelength range can optimize the detection effect of the light signal and reduce the influence of interfering light. POPOP has good photostability under light irradiation and can maintain its fluorescence performance during long-term use. This means that during long-term use, the scintillator can stably emit fluorescence signals, reducing the decline in detection performance caused by fluorescence attenuation. POPOP has good solubility and compatibility in the plastic matrix, and can be evenly dispersed in the matrix to ensure the uniformity of the light emission of the scintillator. Good dispersion avoids the aggregation of fluorescent dyes in the matrix, thereby maintaining stable light emission performance.

[0089] Wave shifter: 1,4-Bis(5-phenyloxazolyl)benzene (DBP) is an effective wavelength shifter that can convert the short-wavelength light signal generated by the scintillator into a longer wavelength light signal. This wavelength shifting function can improve the light signal transmission efficiency of the scintillator and reduce the loss of light signals during transmission. The wavelength shifting function of DBP makes the generated light signal more consistent with the response range of the detector, thereby improving the working efficiency and detection sensitivity of the detector. By matching the optimal response wavelength of the light detector, the performance of the overall detection system can be improved. Wave shifters can help reduce light loss when the light signal propagates inside the plastic scintillator, thereby improving the light collection efficiency. It can effectively transmit more light signals to the photosensitive detector by reducing the scattering loss of light signals inside the scintillator. The use of wave shifters helps to improve the photostability of plastic scintillators in various usage environments. DBP can provide additional stability in the optical properties of the scintillator, so that the intensity and wavelength of the light signal remain consistent during long-term use.

[0090] Photoconductivity enhancer: Dimethylsiloxane, as a photoconductivity enhancer, plays an important photoconductivity function in plastic scintillators. It can help the light signal inside the plastic scintillator to be more effectively guided to the photosensitive detector, thereby improving the light collection efficiency. Dimethylsiloxane has excellent optical transparency, which enables the light signal to maintain a low attenuation inside the scintillator. Dimethylsiloxane can form a uniform photoconductivity network in the plastic scintillator to ensure the uniform distribution of the light signal inside the scintillator. This uniformity is crucial to reducing the aggregation effect of the light signal and improving the accuracy of light detection. Since dimethylsiloxane has good photoconductivity, it can effectively reduce the scattering and absorption loss of light inside the plastic scintillator. This function of reducing light loss helps to improve the light collection efficiency and overall detection performance of the plastic scintillator. Dimethylsiloxane has good dispersion in the plastic scintillator and will not cause aggregation or uneven distribution of the photoconductivity enhancer. This stability helps to maintain the photoconductivity of the plastic scintillator in long-term use and ensures that it can work stably under various environmental conditions.

[0091] The plastic scintillators obtained from Examples 1-3 and Comparative Examples 1-3 were tested, and the test data are shown in the data recording table.

[0092] Table 1 Data record table

[0093]

[0094]

[0095] It should be noted that the light collection efficiency (%) detection method is: use a standard light source and light detector (such as a photodiode or photomultiplier tube), place them on both sides of the plastic scintillator, and measure the light intensity under different photoconductivity enhancer configurations. The light collection efficiency can be calculated by comparing the light intensity using different photoconductivity enhancers with the reference light intensity (the light intensity without enhancer). The experiment was carried out under standard laboratory conditions to ensure the stability of the light source and detector. The data was obtained by repeated testing of multiple samples.

[0096] Light guide uniformity test method: Use a scanning light intensity measurement device (such as a scanning fiber detector) to perform a uniformity scan on the surface of the plastic scintillator. Light intensity uniformity is evaluated by measuring the light intensity in different areas of the surface and calculating the standard deviation of the light intensity. The experiment is carried out under uniform light source conditions to ensure the accuracy of the measurement. The light guide uniformity grade is determined by a standardized light intensity uniformity scoring system (1 is the worst and 5 is the best).

[0097] Light attenuation refers to the degree of reduction in the light output intensity of a plastic scintillator during long-term use. The following is the measurement method:

[0098] Prepare multiple identical plastic scintillator samples and measure the initial fluorescence intensity of the samples using a spectrometer or photosensitive detector under standardized excitation conditions. Record the initial light output intensity value.

[0099] The samples are exposed to a simulated actual use environment by continuously irradiating the light source (simulating the excitation of charged particles) for a long time. At predetermined time intervals (every 100 hours), the light output intensity measurement is repeated using the same measurement equipment and method.

[0100] Calculate the light attenuation rate:

[0101] The light attenuation rate is calculated based on the measured light output intensity over time. The light attenuation rate can be calculated using the following formula:

[0102] Light attenuation rate = (initial light output intensity - current light output intensity) / initial light output intensity * 100%;

[0103] From Table 1, we can see that the light collection efficiency is:

[0104] The light collection efficiency of Example 1 is 91%, the light collection efficiency of Example 2 is 93%, and the light collection efficiency of Example 3 is 89%. These values ​​are significantly higher than the efficiency of the comparative example group. In particular, the 93% light collection efficiency of Example 2 is the highest among all the solutions, which shows that the configuration using dimethylsiloxane as a photoconductivity enhancer has the best effect and can effectively improve the light collection ability.

[0105] In comparison, the light collection efficiency of Comparative Example 1 is 72%, Comparative Example 2 is 67%, and Comparative Example 3 is 74%. These values ​​are low, indicating that traditional optical enhancers (such as optical fibers, silica, optical coatings) are not as effective as new technology solutions in improving light collection efficiency. Traditional optical enhancers usually require additional processing steps, which may cause light loss or physical damage to the optical fiber, thereby reducing the light collection efficiency.

[0106] Light guide uniformity

[0107] The light guide uniformity of all embodiments is 5, indicating that they have the best performance in terms of light guide uniformity. This means that the light guide enhancers (especially dimethylsiloxane) in these schemes can be evenly dispersed in the plastic scintillator, ensuring uniform light output, thereby improving the light detection accuracy.

[0108] In the comparative example group, the photoconductivity uniformity of comparative example 1 is 3, that of comparative example 2 is 2, and that of comparative example 3 is 3. The photoconductivity uniformity is poor, especially that of comparative example 2 is the lowest, indicating that the conventional photoconductivity enhancer performs poorly in terms of photoconductivity uniformity. The uniform distribution of the photoconductivity enhancer is crucial to the performance of the scintillator, and poor uniformity may lead to uneven detection of light, affecting the overall detection effect.

[0109] Light attenuation rate

[0110] The light attenuation rate of Example 1 is 5.2%, that of Example 2 is 4.8%, and that of Example 3 is 4.5%. These light attenuation rates are all lower than those of the comparative example group, especially that of Example 3 is the lowest (4.5%), indicating that the light output is better maintained during long-term use and has higher stability. This shows that the dimethylsiloxane in the new technology solution is effective as a light guide enhancer in reducing light attenuation and can extend the service life of the plastic scintillator.

[0111] In the comparative example group, the light attenuation rate of comparative example 1 is 7.8%, that of comparative example 2 is 6.5%, and that of comparative example 3 is 9.2%. The light attenuation rate is relatively high, especially that of comparative example 3 is the highest (9.2%), indicating that the traditional photoconductive enhancer is less effective in reducing light attenuation. This may be due to the uneven dispersion of the traditional enhancer or the unstable performance during use, which leads to a faster reduction in light output intensity, thereby affecting the long-term stability of the scintillator.

[0112] In summary:

[0113] Light collection efficiency: In Examples 1-3, the configuration using dimethylsiloxane as a light guide enhancer significantly improves the light collection efficiency, especially Example 2 performs best. This shows that the new solution is better than the traditional method in improving the light collection ability.

[0114] Light guide uniformity: All examples have a light guide uniformity of 5, showing the significant advantages of the new technology in terms of light distribution uniformity. The uniformity of traditional light guide enhancers is poor, which affects the light detection effect.

[0115] Light attenuation rate: Examples 1-3 are superior to the comparative example group in terms of light attenuation rate, especially Example 3 which has the lowest light attenuation rate, indicating that the photoconductive enhancer in the new solution can effectively extend the service life of the plastic scintillator and reduce the attenuation of light output.

[0116] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A plastic scintillator, characterized in that: include: Matrix, fluorescent dye, wave shifter and photoconductivity enhancer; Matrix: copolymer of polymethylphenylsiloxane and polymethylphenylmethylhydrogensiloxane; Fluorescent dye: 3-(Benzoxazole)-6-(phenyl)benzoxazole; Wave shifter: 1,4-bis(5-phenyloxazole)benzene; and photoconductivity enhancers: dimethylsiloxane; The light guide enhancer accounts for 0.1-0.3% of the mass of the plastic scintillator.

2. The plastic scintillator according to claim 1, characterized in that: The mass ratio of polymethylphenylsiloxane to polymethylphenylmethylhydrogensiloxane in the matrix is ​​8:

2.

3. The plastic scintillator according to claim 1, characterized in that: The molecular weight of polymethylphenylsiloxane is 10000-30000, and the molecular weight of polymethylphenylmethylhydrogensiloxane is 5000-20000.

4. The plastic scintillator according to claim 1, characterized in that: The fluorescent dye accounts for 5-7% of the mass of the plastic scintillator, and the wave shifter accounts for 0.05-0.15% of the mass of the plastic scintillator.

5. A method for preparing a plastic scintillator according to any one of claims 1 to 4, characterized in that: The following steps are involved: Mixing polymethylphenylsiloxane and polymethylphenylmethylhydrogensiloxane at a mass ratio of 8:2 and stirring for 30-60 minutes to obtain component A; Dissolving a fluorescent dye, a wave shifter and a photoconductivity enhancer in an organic solvent to obtain component B; stirring the component A and component B under a vacuum environment for 1-2 hours to obtain a mixed solution; placing the mixed solution in a vacuum degassing tank, and using a vacuum pump to extract bubbles in the liquid; Benzoyl peroxide is added as a catalyst and placed in a mold for thermal curing to obtain the plastic scintillator.

6. The method for preparing a plastic scintillator according to claim 5, characterized in that: The organic solvent is toluene or xylene.

7. The method for preparing a plastic scintillator according to claim 5, characterized in that: The vacuum degree in the vacuum degassing tank is adjusted to 50-100 Pa, and the degassing time is 30-60 min.

8. The method for preparing a plastic scintillator according to claim 5, characterized in that: The amount of benzoyl peroxide used is 0.5-1% of the total mass of the mixed solution.

9. The method for preparing a plastic scintillator according to claim 5, characterized in that: In the thermal curing, the initial temperature is 35-40° C., the heating is performed at a heating rate of 10-15° C. / h, and the heating time is 4-6 hours.

10. The method for preparing a plastic scintillator according to claim 5, characterized in that: The thermal curing is performed in a sealed environment.